Pac13 is a Small, Monomeric Dehydratase that Mediates the Formation of the 3′‐Deoxy Nucleoside of Pacidamycins. Issue 41 (30th August 2017) - Michailidou, Freideriki; Chung, Chun‐wa; Brown, Murray J. B.; Bent, Andrew F.; Naismith, James H.; Leavens, William J.; Lynn, Sean M.; Sharma, Sunil V.; Goss, Rebecca J. M.
Abstract: The uridyl peptide antibiotics (UPAs), of which pacidamycin is a member, have a clinically unexploited mode of action and an unusual assembly. Perhaps the most striking feature of these molecules is the biosynthetically unique 3′‐deoxyuridine that they share. This moiety is generated by an unusual, small and monomeric dehydratase, Pac13, which catalyses the dehydration of uridine‐5′‐aldehyde. Here we report the structural characterisation of Pac13 with a series of ligands, and gain insight into the enzyme's mechanism demonstrating that H42 is critical to the enzyme's activity and that the reaction is likely to proceed via an E1cB mechanism. The resemblance of the 3′‐deoxy pacidamycin moiety with the synthetic anti‐retrovirals, presents a potential opportunity for the utilisation of Pac13 in the biocatalytic generation of antiviral compounds. Abstract : Short and sweet : Pac13, a small, monomeric and cofactor‐independent dehydratase, catalyzes the formation of biosynthetically unique 3′‐deoxyuridine, a similar moiety to that present within synthetic retrovirals. Structural and mechanistic insights are reported.